Cross-Cultural Adaptation and Validation of the Persian Version of the M. D. Anderson Dysphagia Inventory - Sharifi, Fardin; Qoreishi, Zahra Sadat; Bakhtiyari, Jalal; Ebadi, Abbas; Houshyari, Mohammad; Azghandi, Samira (International Archives of Otorhinolaryngology, 2024)
Introduction Dysphagia is a common issue in patients with head and neck cancer (HNC) and is known to negatively impact their quality of life. To evaluate the impact of dysphagia on the quality of life of HNC patients, the M. D. Anderson Dysphagia Inventory (MDADI) questionnaire was developed.Objective The present study aimed to culturally adapt and validate the MDADI for Persian-speaking individuals. The MDADI is a self-administered questionnaire designed to assess the impact of dysphagia on the quality of life of HNC patients.Methods The original MDADI questionnaire was translated into Persian using the forward-backward method, following the guidelines of the World Health Organization (WHO) for cultural adaptation. The content validity of the Persian version, MDADI-P, was assessed by 10 speech-language pathologists using the content validity index (CVI). Seventy-five HNC patients completed the MDADI-P to evaluate its convergent validity, which was determined by comparing the results with the Short-Form 36 (SF-36) questionnaire. Internal consistency and test-retest reliability were assessed using Cronbach α coefficient and intraclass correlation (ICC), respectively.Results The scale content validity index (S-CVI) for the MDADI-P was 0.90, indicating good content validity. The MDADI-P demonstrated satisfactory internal consistency (Cronbach α coefficient = 0.728) and test-retest reliability (ICC = 0.91). The total MDADI-P score exhibited a significant correlation with the physical and mental components of the SF-36 (0.456 and 0.349, respectively, p < 0.05).Conclusion The findings of the present study confirm the suitability of the MDADI-P in terms of content validity, construct validity, internal consistency, and test-retest reliability.
Keywords: M. D. Anderson dysphagia inventory; dysphagia; head and neck cancer; quality of life